2021
DOI: 10.35683/jcm20078.113
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship orientation and business discontinuance: A relationship analysis of total early-stage activities in the BRICS countries

Abstract: Purpose of the study: The links between entrepreneurial orientation (EO) and business discontinuance are seldom researched. This article analyses EO and business discontinuance rates in the countries of Brazil, Russia, India, China and South Africa (SA) of which the acronym is BRICS. The study aim is to establish whether innovative management of SMEs increase business survival rates. The BRICS formed in 2009-2010 but research comparing their SME sectors are sparse. Theoretically, EO underscored by innovation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 33 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Concordant with the literature, as opposed to the notion that businesses will ascribe their failure to external antecedents, empirical findings showed that management deficiency is the primary reason for business failure. It is more of the internal factors why businesses exit and discontinue parallel to the studies reviewed (Bushe, 2019;Martinez et al, 2019;Bunyaminu et al 2019;Davies, C., & van Vuuren, 2021). Moreover, all the respondents believed that owner/founder orientation, structural or firm issues, and financial conditions are the internal factors that lead to business failure and exit.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Concordant with the literature, as opposed to the notion that businesses will ascribe their failure to external antecedents, empirical findings showed that management deficiency is the primary reason for business failure. It is more of the internal factors why businesses exit and discontinue parallel to the studies reviewed (Bushe, 2019;Martinez et al, 2019;Bunyaminu et al 2019;Davies, C., & van Vuuren, 2021). Moreover, all the respondents believed that owner/founder orientation, structural or firm issues, and financial conditions are the internal factors that lead to business failure and exit.…”
Section: Discussionmentioning
confidence: 93%
“…Extant literature attributed these to human capital and knowledge or the owner/founder orientations which encompass motivations, skills or management deficiencies, capabilities, characteristics/behavior, and financial knowledge shortcomings (Bushe, 2019;Martinez et al, 2019;Bunyaminu et al 2019). The competency and the leadership style of the management are significant factors for organizational performance (Davies, C., & van Vuuren, 2021). Lack of entrepreneurial skills as a difficulty in starting and managing their firms during their early stages is a major cause of business failure for small businesses (Bushe, 2019).…”
Section: Internal Factorsmentioning
confidence: 99%
See 3 more Smart Citations